Integrasi Ekowisata Berbasis Pesisir: Strategi Peningkatan Nilai Ekonomi Dan Lingkungan - Mochamad Ridwan; Eka Dewi Anggraini (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
The lack of integration of the ecotourism management system often causes problems in the attraction aspect, resulting in a decrease in tourist visits both regionally, nationally and internationally. The main objective of the research is to develop a strategy to increase economic and environmental value in the form of integrating three coastal-based ecotourisms. The data used are primary data (qualitative data) and secondary data (quantitative data). The Bengkulu City was used as an urban-based research case with coastal characteristics. The three ecotourism objects taken are Fort Marlborough ecotourism, Kampong Cina ecotourism, and Pantai Panjang ecotourism. Data collection was carried out using in-depth interviews, observation, and documentation methods. Data analysis was carried out using descriptive analysis methods and SWOT analysis. The results of the research show that there are nine strategies that are capable of building coastal-based integrated ecotourism that is highly attractive and capable of increasing economic and environmental value, namely: formulate a grand design for the integration of three coastal ecotourism destinations appropriately; build strong coordination and synergy with various stakeholders; improve the charm of the physical form of ecotourism consistently; provide strengthening, literacy, and guidance to the community; conduct an in-depth study of the various shortcomings of the three destinations; building a positive image of integrated coastal ecotourism destinations; increasing the strength of attraction through improving the quality of representative economic facilities/facilities (culinary tourism); improving the quality of human resources in the form of training and benchmarking to increase professionalism; and conducting intensive dialogue and discussions between stakeholders.